Cholesterol-lowering pattern affects the progression of atherosclerosis in apolipoprotein E deficient mice - Yusuke Masuda; Shinji Yamaguchi; Tomohiro Nishizawa (Elsevier, 2016)
Although the importance of LDL cholesterol lowering is widely recognized, the impact of the cholesterol-lowering pattern on the atherosclerosis remains unclear. Here, we used cholestyramine in apolipoprotein E deficient mice in two different regimens to induce a see-saw shaped or a sustained cholesterol reduction, with the trough of cholesterol comparable. After 12 weeks-treatment, a sustained cholesterol reduction exhibited a smaller atherosclerotic area. Moreover, we observed a correlation between the area under the curve of plasma cholesterol and the atherosclerotic area. These results suggest that the sustained cholesterol reduction is beneficial for preventing the progression of atherosclerosis in cholesterol lowering therapy.